IMPROVING PRIMARY SCHOOL STUDENTS’ KNOWLEDGE OF PUBERTY THROUGH CONTEXTUAL TEACHING AND LEARNING METHOD - Nurfadhilah .; Dewi Andayani; Putri Indah Pratiwi; Rika Sa'diyah; Erry Utomo; Nurjannah Achmad (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
The Indonesian adolescents’ knowledge on the subject of puberty is very limited according to a national data survey. This is the reason this study aims to increase knowledge, attitudes, and behaviors of healthy living during the puberty phase through the contextual teaching and learning (CTL) method of classroom action research with cyclical procedures. The participants were 20 students and a teacher of fifth-year at the elementary school; meanwhile, the object was knowledge about puberty, collected through test questions and observations. The data analysis technique was conducted in a quantitative and qualitative descriptive manner, and the result showed that the method used was able to improve the knowledge, attitudes, and healthy living behavior of fifth-grade students in SDIT Mutiara Insan. This is evident in the pre-cycle with a percentage of 5.3%, which further increased to 15.8% in the first cycle, while in the second cycle, it increased to 94.7%.